Risk of Musculoskeletal Disorders (MSDs) in Insurance Company Workers - Nur Afifah Dwi Laksana Putri; Dewi Purnamawati (Jurnal Dunia Kesmas, 2026)
Musculoskeletal Disorders (MSDs) are a common occupational health problem experienced by office workers, particularly due to prolonged static work postures and high-intensity computer use. This study aims to identify MSD complaints among workers at Insurance Company  using the Nordic Musculoskeletal Questionnaire (NMQ). The study was conducted using a descriptive quantitative approach with 35 respondents selected based on inclusion criteria. The results showed that 94.3% of respondents experienced MSD complaints, while 5.7% of respondents did not report any complaints. MSD complaints were most commonly found in body parts vulnerable to exposure to ergonomic risks, namely the neck, shoulders, upper and lower back, and wrists. The high proportion of these complaints indicates that the risk of MSDs in the Insurance Company work environment is at a level that requires serious attention. These findings demonstrate the need for ergonomic interventions as part of efforts to prevent occupational diseases in the office sector through rearranging workstations, implementing microbreaks, providing ergonomic education, and regular monitoring of working conditions to reduce the risk of MSDs and improve work comfort.